Diverse TRPV1 responses to cannabinoids. Issue 1 (1st January 2019) - Starkus, J.; Jansen, C.; Shimoda, L. M. N.; Stokes, A. J.; Small-Howard, A. L.; Turner, H.
ABSTRACT: Cannabinoid compounds are potential analgesics. Users of medicinal Cannabis report efficacy for pain control, clinical studies show that cannabis can be effective and opioid sparing in chronic pain, and some constituent cannabinoids have been shown to target nociceptive ion channels. Here, we explore and compare a suite of cannabinoids for their impact upon the physiology of TRPV1. The cannabinoids tested evoke differential responses in terms of kinetics of activation and inactivation. Cannabinoid activation of TRPV1 displays significant dependence on internal and external calcium levels. Cannabinoid activation of TRPV1 does not appear to induce the highly permeant, pore-dilated channel state seen with Capsaicin, even at high current amplitudes. Finally, we analyzed cannabinoid responses at nociceptive channels other than TRPV1 (TRPV2, TRPM8, and TRPA1), and report that cannabinoids differentially activate these channels. On the basis of response activation and kinetics, state-selectivity and receptor selectivity, it may be possible to rationally design approaches to pain using single or multiple cannabinoids.